Internet connectivity disruption in Czech Republic (Czechia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Czechia. Data sourced from IODA.
Network Disruption Incident ID: CZ-2026-0006. Severity: critical. Confidence: 65%